Urgensi Pengaturan Hukum Pelarangan Propaganda Homoseksual di Indonesia (RechtJiva, 2024)
This study aims to examine the urgency of legal regulation concerning the prohibition of homosexual propaganda in Indonesia, which is perceived by the majority of society as a violation of social and religious values. The research employs a normative juridical method with an approach based on analysis of legislation, legal literature, and expert opinions. Data sources include primary documents such as the 1945 Constitution, the Criminal Code, and the 2024 ITE Law, as well as secondary data from legal literature and academic studies. The analysis is conducted from philosophical, juridical, and sociological perspectives, highlighting regulatory gaps in Indonesia and comparing them with the legal framework in Uganda. The findings indicate that homosexual propaganda contradicts the philosophical values embodied in Pancasila, reveals a legal vacuum within Indonesia’s criminal justice system, and reflects diverse collective societal views on the phenomenon from a sociological aspect. Accordingly, the researcher formulates an ideal legal regulatory concept that can serve as a reference for the government and policymakers to prevent broader social impacts and protect societal norms.